1997
DOI: 10.2307/3579630
|View full text |Cite
|
Sign up to set email alerts
|

Lymphomas in Eμ-Pim1 Transgenic Mice Exposed to Pulsed 900 MHz Electromagnetic Fields

Abstract: Whether radiofrequency (RF) fields are carcinogenic is controversial; epidemiological data have been inconclusive and animal tests limited. The aim of the present study was to determine whether long-term exposure to pulse-modulated RF fields similar to those used in digital mobile telecommunications would increase the incidence of lymphoma in E mu-Pim1 transgenic mice, which are moderately predisposed to develop lymphoma spontaneously. One hundred female E mu-Pim1 mice were sham-exposed and 101 were exposed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
199
4
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 333 publications
(216 citation statements)
references
References 38 publications
8
199
4
5
Order By: Relevance
“…MCV values of mice in 0.9 GHz exposed group increased with prolonged exposure while mice in the 1.8 GHz exposed group are on the contrary. These results are in agreement with previous studies done by [16] which reported that long-term intermittent exposure to EMF can enhance the probability that mice carrying a lymphomagenic oncogene will develop lymphomas. Significant decrease was also recorded related to RBCs, HB, and HT, MCV and MCH compared to the control group.…”
Section: Mchc For Exposed and Sham Exposed Groupssupporting
confidence: 83%
See 2 more Smart Citations
“…MCV values of mice in 0.9 GHz exposed group increased with prolonged exposure while mice in the 1.8 GHz exposed group are on the contrary. These results are in agreement with previous studies done by [16] which reported that long-term intermittent exposure to EMF can enhance the probability that mice carrying a lymphomagenic oncogene will develop lymphomas. Significant decrease was also recorded related to RBCs, HB, and HT, MCV and MCH compared to the control group.…”
Section: Mchc For Exposed and Sham Exposed Groupssupporting
confidence: 83%
“…This restrained position is reported causing stress related changes in [17,20] and imposes constraints on behavior and brain development of the animals [21]. The study of long term effect in this condition is also not appropriate as no exposures per day and per week will be identical leading to serious comparative difficulties as reported in [16,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When replicated, however, even those studies were found to be non reproducible. One well-known example is the study by Repacholi et al (1997)who have reported higher incidences of lymphoma in transgenic mice which were exposed to pulsed EMF at 900 MHz (Repacholi et al 1997). Two independent replication studies did not conWrm the earlier Wndings (Oberto et al 2007; Utteridge et al 2002).…”
Section: Introductionmentioning
confidence: 97%
“…However, the results of these studies are conflicting. Some have implicated an increased health risk [1], but most studies have shown no effects [2]. The lens epithelial cells (LECs) are a single layer of cuboidal cells at the anterior surface of the lens, which retain the proliferative capacity and are important for maintaining the metabolic homeostasis and transparency of the lens.…”
Section: Dear Editormentioning
confidence: 99%